Who is most vulnerable to social rejection? The toxic combination of low self-esteem and lack of negative emotion differentiation on neural responses to rejection. - Todd B Kashdan; C Nathan Dewall; Carrie L Masten; Richard S Pond; Caitlin Powell; David Combs; David R Schurtz; Antonina S Farmer (PLoS ONE, 2014)
People have a fundamental need to belong that, when satisfied, is associated with mental and physical well-being. The current investigation examined what happens when the need to belong is thwarted-and how individual differences in self-esteem and emotion differentiation modulate neural responses to social rejection. We hypothesized that low self-esteem would predict heightened activation in distress-related neural responses during a social rejection manipulation, but that this relationship would be moderated by negative emotion differentiation-defined as adeptness at using discrete negative emotion categories to capture one's felt experience. Combining daily diary and neuroimaging methodologies, the current study showed that low self-esteem and low negative emotion differentiation represented a toxic combination that was associated with stronger activation during social rejection (versus social inclusion) in the dorsal anterior cingulate cortex and anterior insula-two regions previously shown to index social distress. In contrast, individuals with greater negative emotion differentiation did not show stronger activation in these regions, regardless of their level of self-esteem; fitting with prior evidence that negative emotion differentiation confers equanimity in emotionally upsetting situations.